Navigating climate awareness in academia: a study of air travel attitudes among international students in Austria - Prandner, Dimitri; Hasengruber, Katrin (Frontiers in Education, 2025)
The urgent need to address climate change has prompted universities to reassess their impact on the environment, as the tension between academic internationalization and sustainability presents a complex challenge on multiple levels; including the organizations themselves, researchers or faculty, and students. The article explores the perceptions and attitudes of international students toward climate change, their personal environmental impact, and their perceptions of internationalization and mobility. To do so a qualitative case study was conducted in Austria (interview study; n = 29), including both bachelor’s and master’s program students. The study aimed to investigate the attitudes of international students toward air travel and identified five distinct types of students with varying levels of awareness and willingness to reflect on their personal impact on climate change. While some students prioritize their personal right to fly and gain experience, neglecting their contribution to climate change, others demonstrate a clear understanding of the need for change. The findings suggest that universities can play a key role in promoting environmental awareness by integrating climate change education into international study programs, providing transparent information about environmental impacts, and incentivizing sustainable mobility. Our aim is to contribute to the ongoing discussions regarding the intersection of higher education, internationalization, and climate change. We emphasize the need for significant institutional changes to address the complexities involved.